2006
DOI: 10.1145/1150334.1150336
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic construction of sets for k -restrictions

Abstract: This work addresses k-restriction problems, which unify combinatorial problems of the following type: The goal is to construct a short list of strings in Σ m that satisfies a given set of k-wise demands. For every k positions and every demand, there must be at least one string in the list that satisfies the demand at these positions. Problems of this form frequently arise in different fields in Computer Science.The standard approach for deterministically solving such problems is via almost k-wise independence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
221
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(226 citation statements)
references
References 21 publications
1
221
0
2
Order By: Relevance
“…However, the game used in the proof of Proposition 6.1 has only one level, one state, and no transitions, so none of these limitations apply to it, and the ILP will find the optimal abstraction for games in that class. The NP-hardness reduction in the proof is from SET COVER, which cannot be approximated in worst-case polynomial time to an approximation ratio better than a constant times ln q unless P = NP [Alon et al 2006]. Therefore, the gap in solution quality-in terms of the size of the (action) abstraction for the level-found by the greedy algorithm (which runs in polynomial time) versus the ILP (which finds an optimal solution in this game class) cannot be bounded by any constant.…”
Section: Bottom-up Single-pass Level-by-level Greedy Abstraction Algomentioning
confidence: 99%
“…However, the game used in the proof of Proposition 6.1 has only one level, one state, and no transitions, so none of these limitations apply to it, and the ILP will find the optimal abstraction for games in that class. The NP-hardness reduction in the proof is from SET COVER, which cannot be approximated in worst-case polynomial time to an approximation ratio better than a constant times ln q unless P = NP [Alon et al 2006]. Therefore, the gap in solution quality-in terms of the size of the (action) abstraction for the level-found by the greedy algorithm (which runs in polynomial time) versus the ILP (which finds an optimal solution in this game class) cannot be bounded by any constant.…”
Section: Bottom-up Single-pass Level-by-level Greedy Abstraction Algomentioning
confidence: 99%
“…This matches the lower bound given by Berlinkov, albeit for alphabets of arbitrary, instead of constant size. However, assuming P = NP, SET COVER has no c · log napproximation for some constant c > 0 [12]. This offers a significant improvement over the previous best lower bound.…”
Section: Resultsmentioning
confidence: 94%
“…Notice that w 1 · · · w l ∈ Σ * is a reset sequence for A if and only if 1≤i≤l S wi is a cover for X. SET COVER has no c log n-approximation for some constant c > 0 unless P = NP [12]. Thus, this lower bound also extends to STACK COVER.…”
Section: The Stack Cover Problemmentioning
confidence: 91%
“…shown that SCP does not admit an o(lg n) approximation under the weaker assumption that P = NP [14,2].…”
Section: Inapproximability Of Minimum Verification Set Problemmentioning
confidence: 99%